An appraisal of compressive force path concept - Singh, Bhupinder; Jangir, Nitesh Kumar (Journal of Structural Engineering, 2024)
An experimental appraisal of compressive force path concept for explaining shear failure of reinforced concrete beams has been carried out in the form of a comparative study of the behaviour of concrete beams reinforced in compliance with this concept and that of beams reinforced in compliance with codal procedures based on the 45° truss analogy. The results of this investigation indicate that the causes of beam failure are associated with stress conditions in the region of the path along which compressive force is transmitted to the supports after the occurrence of diagonal cracking. Though placing of transverse reinforcement in the shear span is inevitable to prevent a premature shear failure such detailing in itself may not be sufficient to provide appreciable ductility. Significant enhancement of ductility was observed in beams in which the transverse reinforcement had been extended from the shear span into the flexure span in compliance with the compressive force path concept.